Federal, state, and district level English language learner program entry and exit requirements: Effects on the education of language minority learners. - Ragan, Alex; Lesaux, Nonie (Education Policy Analysis Archives, 2006)
Identification of a language minority learner for placement in a program for English Language Learners (ELLs), and the length of the support program, may have a significant effect on the student’s academic achievement. Widespread anecdotal evidence suggests that criteria used to make placement decisions vary widely across the U.S. This study systematically examines related federal laws and guidance, as well as published entry and exit criteria for ELL programs for the 10 states and 10 districts in the U.S. with the largest enrollment of ELLs. For the majority of placement decisions, a measure of English language proficiency is used. Very few states and districts rely on multiple sources of information for these decisions. The ramifications of these findings are discussed in light of the language and content demands of the mainstream classroom.